(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Due to its ecological, India is the second most vulnerable country in the world to natural disasters likecyclones, earthquakes, droughts, rain falls, hurricanes, and so on. Between 2000 and 2009, disasters affected 65 million people, and between 2012 and 2019, the mortality rate was 79732. Disaster management is a four-step process that requires all levels of government organisations to plan, prepare, and respond to any natural disaster. The review material was collected from online databases, i.e., Research Gate, PubMed, Scopus, CINHAL, and Google Scholar. During disaster management, the nurse's role includes decisive the extent of the event, prioritise the health needs of affected people, identifying actual and potential health problems, and estimating the resources required to respond to the psychological, physical, economical and other needs identified.